Correlative Analysis Between Adverse Events of Preoperative Chemotherapy and Postoperative Complications of Gastric Cancer - Wu, Zhouqiao; Wang, Yiding; Hou, Shiyang; Wang, Qi; Li, Bailong; Ying, Xiangji; Li, Shuangxi; Li, Ziyu; Ji, Jiafu (Frontiers in Surgery, 2021)
BACKGROUND and OBJECTIVES: This study aims to explore the safety of preoperative chemotherapy and clarify whether preoperative chemotherapy with SOX (oxaliplatin + S-1) regimen and its adverse events are associated with higher risks of postoperative complications. METHODS: We included consecutive patients with gastric cancer who underwent gastrectomy in our department between July 1st 2018, and January 31st 2020. Patients with preoperative SOX regimen chemotherapy were included in the analysis. RESULTS: In the 343 included patients, 77 cases underwent preoperative chemotherapy. In total, surgical complications were found in 117 patients (34.1%), and there was no significant difference between the patients with and without preoperative chemotherapy before and after propensity score matching (p>0.05, respectively). Multivariate analysis showed that preoperative comorbidities (p=0.026) and the preoperative cT4b (p=0.028) were independent risk factors for postoperative complications. In patients with preoperative chemotherapy, neither the occurrence of adverse events nor their severity was associated with postoperative complications (p>0.05). However, patients who received 5-6 cycles were more prone to postoperative complications than those who received 3-4 cycles (62.5% vs. 27.9%, OR=4.306, 95% Cl=1.282-14.464, p=0.018). CONCLUSIONS: Occurrence of postoperative complications was not influenced by preoperative SOX chemotherapy. However, increased cycles of chemotherapy may lead to higher incidence of postoperative complications.